Optimized Encryption Algorithm using Dynamic Keys - Mittal, Hitesh (My University, 2014)
Abstract Data security is an essential component of an organization in order to keep the information safe from various competitors. It helps to ensure the privacy of a user mation from others. Secured and timely transmission of data is always an important aspect for an organization. Strong encryption algorithms and optimized key management techniques always help in achieving confidentiality, authentication and integrity of data and reduce the overheads of the system. Keeping in view the importance of dynamic keys for secure data transmission, the work is focused on the use of dynamic keys for data security. In this work various encryption algorithms have been studied. Literature Survey has been carried out by incorporating key papers related to data encryption. From the literature survey; gaps and observation have also been drawn. RSA is critically analyzed and key management has also been optimized. Simulation results have been achieved using MATLAB 7.3; results prove that the proposed algorithm is optimized compared to RSA in terms of hacking and processing time. Finally, conclusion and future work has also been stated at the end of thesis.
ME, ECED
Keywords: Data Encryption